Defensive Changes in Corporate Payout Policy: Share Repurchases and Special Dividends - Denis, David J. (Journal of Finance, 1990)
This paper examines defensive payouts announced in response to hostile corporate control activity. The evidence indicates that the announcement of defensive share repurchases is associated with an average negative impact on the share price of the target firm. In contrast, special dividend payments generally increase the wealth of target firm shareholders. Regardless of payout type, those firms remaining independent after the outcome of the corporate control contest experience an abnormal share price increase over the duration of the contest. Among these firms there are substantial post-contest changes in capital, asset, and ownership structure and abnormally high rates of top management turnover.